(untitled) (Research, Society and Development, 2021)
The objective was to analyze the scientific evidence on the repercussions of the coronavirus pandemic on the mental health of nursing professionals. A systematic review study was carried out. For the search, a data collection was carried out by searching the Virtual Health Library (VHL) in the electronic databases used in the research: PubMed (National Library of Medicine of the National Institute of Health of the United States), SCIELO (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature on Health Sciences), BDENF (Nursing Database), and Academic Google, from 2020 to 2021. The descriptors “Covid-19” were used; “Pademics”; “infections”; "Mental health"; "Nursing". A total of 358 articles related to the topic were found. Soon after, the inclusion and exclusion criteria were applied, leaving 63 articles. 37 studies were selected to compose this systematic review. In view of the results, the studies showed great impacts on the mental health of these employees, which led to the development of depression, anxiety, burnout syndrome and post-traumatic stress. From the analyzed articles, 3 categories emerged: Nursing in the context of the Covid-19 pandemic; Impacts on the mental health of nursing professionals during the Covid-19 pandemic; Support resources for nursing professionals in coping with Covid-19, for discussion of the subject. It is concluded that this research was possible to emphasize the importance of nursing professionals in dealing with the new coronavirus, which is more at the same time exhausting due to several factors such as the devaluation of these employees, causing several impacts on the psychological illness of these workers.